Analisis Pengaruh Ukuran Perusahaan, Leverage Dan Profitabilitas Terhadap Tax Evoidance Pada Bank Riau Kepri Tbk - Viola Syukrina E. Janrosl; Dian Efriyenti; Dedi Riyanto (Prosiding, 2018)
Tax avoidance is an arrangement to minimize or eliminate the tax burden by considering the tax consequences. The case of BCA's objection to the tax correction made by the Directorate General of Tax (DGT). BCA considers that the DJP correction on fiscal profit of Rp 6.78 trillion should be reduced by Rp 5.77 trillion. Reason of BCA for having transfer asset transactions to IBRA. Where indication leads to tax avoidance. This study aims to test and provide empirical evidence of the influence between firm size, profitability and leverage against tax avoidance at Bank Riau Kepri Islands. This type of research is categorized in causative research. The population in this research is Bank Riau Kepri in 2015-2017. Sample selection by purposive sampling method. The data used in this research is secondary data obtained from www.idx.co.id. Data collection techniques with documentation techniques. The data were analyzed by multiple regression analysis with SPSS 22. The test result showed that firm size measured by CETR had significant influence on Tax avoidance, Leverage measured by debt equity ratio (DER) had positive and significant influence on Tax avoidance (Y) and Profitability as measured by Return On Assets (ROA) have a significant effect on Tax avoidance (Y). For further research should add other variables that affect the tax avoidance of companies such as ownership structure and audit committee.